Dexmedetomidine as a Procedural Sedative for Percutaneous Tracheotomy: Case Report and Systematic Literature Review - Jerrold L. Perrott; Michelle T. Co; Steven C. Reynolds; Derek J. R. Gunning (Case Reports in Critical Care)
Purpose. To describe the successful use of dexmedetomidine as the primary procedural sedative for a percutaneous tracheotomy procedure and to systematically present the supporting literature. Materials and Methods. A Case report of our experience and systematic literature search. PubMed, Embase, and Google Scholar were searched without restriction using the key words dexmedetomidine, percutaneous tracheotomy, and tracheotomy procedure. All relevant published references were retrieved irrespective of their methodological quality. Results. In total, only 3 relevant references were found. These include one small placebo controlled randomized trial and 2 case reports. The randomized, placebo controlled trial enrolled patients already sedated on midazolam and included 64 total patients. The 2 other case reports both described the use of dexmedetomidine as the primary procedural sedative. All of the cases reported the successful completion of the percutaneous tracheotomy without any major complication, but none reported the subjective patient experience. Conclusion. Based on the available published literature and our experience, we suggest that dexmedetomidine be considered for use as the primary procedural sedative for percutaneous tracheotomy procedure. Dexmedetomidine’s ability to provide adequate sedation and amnesia, without blunting the respiratory drive and protective reflexes of the patient, may make it an optimal agent in specific cases.